Taxonomy, phylogeny, and distribution of Bronchocela rayaensis (Squamata: Agamidae) on the Thai-Malay Peninsula - Grismer, L. Lee; Wood, Perry L. Jr; Aowphol, Anchelee; Cota, Michael; Murdoch, Mathew L.; Aguilar, César; Grismer, Marta S. (Zootaxa, 2016)
An integrative taxonomic analysis used to identify a new population of Bronchocela from Phuket Island, Thailand indicates it is conspecific with B. rayaensis from the Langkawi Archipelago of northwestern Peninsular Malaysia. An additional specimen photographed from Khura Buri District, Phang-nga Province is also considered to be B. rayaensis and represents a northern range extension of 295 km from the Langkawi Archipelago.